Juridical Analysis of Court Decision No. 16/PID.SUS/2019/PN.Drh Regarding Criminal Sanctions For Teachers Who Do Violent Acts Against Students - Asri Widya Trisnani; Emy Rosnawati (Universitas Muhammadiyah Sidoarjo, 2021)
This study looks at efforts to identify and analyze the juridical selection of the courtroom Number 16PID.SUS/2019/PN.Drh regarding Criminal Sanctions for Teachers Who Do Violence Against Students. And to find out and analyze the correctional basis used by judges in formulating decisions and making choices of punishment in their choices. The form of this research includes juridical-normative research, with a case approach, primary prison substance regulations Number 35 of 2014 concerning Amendments to Regulation Number 23 of 2002 concerning Infant Safety, Regulation Number 14 of 2014 2005 concerning Teachers and Lecturers. And Court Decision Number 16/PID.SUS/2019/PN.Drh, Deductive Information Analysis. The results of this study indicate that the juridical analysis of the selection of case files Number 16/PID.SUS/2019/PN.Drh concerning Criminal Sanctions for Teachers Who Do Violence against Students is not in accordance with the applicable laws and regulations. and policies, the basis of imprisonment used by judges in preparing decisions and sentencing in optional decisions, including the law on honorary teachers and teachers 14 of 2015 article 2 paragraph (4) and (five), then article 39 of a government regulation. Law of the Republic of Indonesia Number 19 of 2017 concerning Teachers and the Purpose for Their Students to Become Great Babies is not a crime.